Challenges of Post-Disaster Reconstruction Projects: An Empirical Investigation According to Project Management Knowledge Areas - Alsaadi, Omimah; Acar, Emrah (American Journal of Management, 2021)
Successful management of post-disaster reconstruction projects (PDRPs) can ensure the efficient use of resources and lead to improved outcomes. The literature on PDRP management is yet in its embryonic stage and systematic research efforts are necessary to address the topic. Paper compares the challenges faced in conventional projects to those in PDRPs according to project management knowledge areas, through an analytical evaluation of the interdependencies between different areas of expertise. A descriptive-exploratory research was designed and qualitative data from interviews with 11 managers with PDRP experience from different countries were analysed. Cause-and-effect relationships between the factors leading to ‘frequent changes in scope,’ ‘time overruns,’ ‘cost overruns,’ and ‘low quality’ were identified. Outputs suggest that managing stakeholders, risks and communications appears critical to cope with an evolving scope, while procurement management has a significant impact on project outcomes due to resource scarcity.